2011
DOI: 10.1371/journal.ppat.1002256
|View full text |Cite
|
Sign up to set email alerts
|

The Human Papillomavirus E6 Oncogene Represses a Cell Adhesion Pathway and Disrupts Focal Adhesion through Degradation of TAp63β upon Transformation

Abstract: Cervical carcinomas result from cellular transformation by the human papillomavirus (HPV) E6 and E7 oncogenes which are constitutively expressed in cancer cells. The E6 oncogene degrades p53 thereby modulating a large set of p53 target genes as shown previously in the cervical carcinoma cell line HeLa. Here we show that the TAp63β isoform of the p63 transcription factor is also a target of E6. The p63 gene plays an essential role in skin homeostasis and is expressed as at least six isoforms. One of these isofo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 48 publications
2
27
0
Order By: Relevance
“…Recently, Khalifa et al, 2011 observed in cervical carcinoma cells, repression of E6/E7 stabilizes the p53 transcription factor leading to activation of a large group of cellular p53 target genes. This evidence show that repression of E6/E7 also induces transcriptional activation of an additional large set of genes involved in cell adhesion including previously described p63 target genes.…”
Section: Clinicopathology Significance Of P53 and P63 Expression In Imentioning
confidence: 99%
“…Recently, Khalifa et al, 2011 observed in cervical carcinoma cells, repression of E6/E7 stabilizes the p53 transcription factor leading to activation of a large group of cellular p53 target genes. This evidence show that repression of E6/E7 also induces transcriptional activation of an additional large set of genes involved in cell adhesion including previously described p63 target genes.…”
Section: Clinicopathology Significance Of P53 and P63 Expression In Imentioning
confidence: 99%
“…Cell fusion studies have shown that anchorage independence of hrHPV-transformed cells relies on a recessive event, suggesting that inactivation of tumor suppressor genes is involved in bypassing anoikis [2]. In support of this, functional loss of tumor suppressive host genes Caveolin-1, SOCS1, TAp63β, LKB1, CADM1, MAL, hsa-miR-34c-3p/5p and hsa-miR-203 was shown to affect anchorage independent growth of HPV-transformed cells [714]. …”
Section: Introductionmentioning
confidence: 99%
“…Upon induction of differentiation, in synchrony with HPV genome amplification and late gene expression, levels of p63 rapidly decrease [Mighty and . Interestingly it has been reported that E6 specifically targets the TAp63β isoform for degradation, with subsequent disruption of focal adhesions, suggesting a novel pathway involved in HPV-induced cell transformation [Ben Khalifa et al, 2011]. E6-mediated p53 degradation has also been reported to downregulate miR-203 levels [McKenna et al, 2010], which may also enhance p63 expression and cell proliferation.…”
Section: Discussionmentioning
confidence: 99%